Relationship development intervention with children, adolescents, and adults : social and emotional development activities for Asperger Syndrome, Autism, PDD and NLD - Gutstein, Steven E. (Jessica Kingsley Pub., 2002)
Remove our emotional bonds with family, colleagues and friends and few of us would want to go on living. Yet establishing and maintaining such bonds is particularly difficult for people on the autism spectrum. This volume contains over 200 enjoyable and stimulating activities and exercises ranging over the entire gamut of social and emotional development, and is applicable to anyone, regardless of diagnosis, but will be particularly valuable for those on the autism spectrum. Activities can be undertaken independently, or with a teacher or therapist, and a full schema for the evaluation of prog.